2019
DOI: 10.5039/agraria.v14i3a6446
|View full text |Cite
|
Sign up to set email alerts
|

Painéis MDP produzidos com resíduos de extração de celulose

Abstract: RESUMO: Muitas alternativas vêm sendo estudadas sobre o emprego de resíduos agrícolas, agroindustriais e florestais na produção de painéis aglomerados na tentativa de aproveitar os resíduos oriundos desses ramos, que por muitas vezes geram problemas ambientais devido à sua destinação incorreta. Dessa forma, este trabalho teve por objetivo avaliar o potencial de utilização do resíduo gerado durante o processo de produção da celulose (UKP), na fabricação de painéis MDP (Medium Density Particleboard). As proporçõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The higher value is considered ideal, because the lignin contributes to the adhesion mechanisms and may contribute to the bonding process of the panels.Regarding the ash,Santos et al (2022) have found a content of 1,20 % close to the present study. However,Andrade et al (2019) obtained a lower content of 0,20 %. High concentrations of this component can block reactive sites for adhesion, affecting the bonding quality and mechanical performance of the panel(Soares et al 2017).For holocellulose,Mendes et al (2014) indicates that Pinus species present a content between 50 % to 85 %, thus the value obtained in this study corresponds to the stipulated range.…”
mentioning
confidence: 84%
“…The higher value is considered ideal, because the lignin contributes to the adhesion mechanisms and may contribute to the bonding process of the panels.Regarding the ash,Santos et al (2022) have found a content of 1,20 % close to the present study. However,Andrade et al (2019) obtained a lower content of 0,20 %. High concentrations of this component can block reactive sites for adhesion, affecting the bonding quality and mechanical performance of the panel(Soares et al 2017).For holocellulose,Mendes et al (2014) indicates that Pinus species present a content between 50 % to 85 %, thus the value obtained in this study corresponds to the stipulated range.…”
mentioning
confidence: 84%
“…reported 20.15% for rice husk and 19.15% for palm trunk. The highest percentage of lignin in miriti is considered satisfactory, as it contributes to adhesion mechanisms and favors the particle bonding process(BUFALINO et al, 2012).Regarding the ash content,Andrade et al (2019a) studied the pinewood and found an average content of 0.20% lower than the respective study. For agricultural residues,Protásio et al (2012) showed higher levels for coffee residues (4.92%) and rice husks (16.78%).…”
mentioning
confidence: 97%